RESEARCH TO CREATE A BIODIVERSITY DATABASE IN THE AREA OF THE CEMENT PLANT «CASPIAN-CEMENT» - Gusman Kenzhetayev; Syrlybekkyzy Samal; Аinur Zhidebayeva (Academic Journal of Physical and Chemical Sciences, 2020)
The result of field studies the state of biological diversity, in order to create a database for monitoring the state of the animal world, on the territory of the existing cement plant. The following taxonomic groups were studied: birds (the largest numerous groups, easily identifiable), mammals (requiring special research methods), reptiles and amphibians. The identification of species that occurred in the study area of the chalk Deposit was carried out and the bio topic requirements for each of these species were studied. Along with the classical methods of environmental assessment and monitoring, a new method for studying biological diversity in the mining area is used. The method is based on geoinformation analysis and mapping data. All data on biodiversity were obtained using a map divided into grid squares (500×500 m), and were collected in a qualitative way (the number of representatives of animal species per grid square). The study area on the South Shetpe Cretaceous Deposit in the area of the plant "Caspian Cement" met with widespread desert species (mole lemming, tushkanchik). In the local fauna there are absolutely no true steppe species, and there are few semi-desert species (small gopher, korsak, saiga). A qualitative assessment of the importance of biodiversity was presented, taking into consideration the landscape-stabilizing factor, maps of "natural habitats". A map of the territory of the cement plant with the site of the chalk quarry with the indication of the natural habitats of biodiversity and their database was compiled.